Determinants of non-interest income in UK commercial banks 2010-2019 - England, James (2020)
This paper used a sample of 85 UK commercial banks to analyse seven possible determinants of non-interest income as a share of operating income resulting in an unbalanced panel data set of 2974 observations over the time period 2013-2019. A fixed effects model was used and generated the following results. With regard to bank specific factors, bank size, represented by natural log of total assets, had a significant negative impact on non-interest income share in contrast to most previous literature. Net interest margin and cost-to-income ratio also had significant, negative relationships whilst macroeconomic factors such as GDP growth and inflation had a significant positive relationship with non-interest income suggesting than non-interest income share may be pro-cyclical. All of these results were found to be significant at the 1% level. Impaired loans / gross loans had a negative relationship and return on average assets, a positive relationship but neither of these were found to be significantly different from zero. Overall, this paper agreed with existing literature in some areas and contradicted it in others. The study concludes by recommending further research into the area, especially regarding the components of non-interest income and how they have changed since the financial crisis. Studying the impacts and determinants of these various components may shed further light on this area of research.